Strengthening of steel I-section beams by wire arc additive manufacturing – concept and experiments - Yang,J; Wadee,MA; Gardner,L (Engineering Structures, 2025)
An experimental investigation to assess the major-axis flexural behaviour of 10 hot-rolled steel I-sectionbeams, strengthened by the addition of material through wire arc additive manufacturing (WAAM) and testedunder either four-point or three-point bending conditions, is presented in this study. The ability of WAAM topre-camber hot-rolled steel I-section beams, as well as to enhance their bending moment resistance and initialelastic stiffness, has been demonstrated. The geometry of the strengthened beam specimens, including theinitial imperfections and pre-camber, were obtained by means of 3D laser scanning. Complementary materialtesting was conducted to obtain the mechanical properties of both the hot-rolled and WAAM steel undermonotonic tensile loading. The experimental results showed that significant pre-cambers of approximately1/200 of the span of the beam could be achieved with only a 2.6% increase in mass. Moreover, increasesof between 11.5% and 33.2% in the ultimate bending moment resistance, and increases of between 8.7%and 35.9% in the initial stiffness, were achieved for increases in mass of between just 2.6% and 12.3%. Thepresented WAAM-strengthening approach can be employed for the strengthening, repair and retrofittingof steel beams in service, as well as for the fabrication of hybrid steel members with improved flexuralbehaviour in new structures.